Without Thought Force the Milky Way Wouldn’t Be the Same—Thought Force in Practice - Lajtner, Tamas (European Scientific Journal, ESJ, 2016)
Thoughts and gravity have common roots. Gravity changes your thoughts, and your thoughts change gravity. How? According to current, widespread understanding, measurable thoughts are electromagnetic signals of the brain. We made a very simple experiment with force of thought using a paper wheel. We concluded that the energy carried by thoughts (expressed in frequency of energy wave) was eight orders of magnitude beyond the highest frequencies of the brain’s electric waves. The brain’s electromagnetic signal doesn’t explain all effects of thought, it is just a part of measurable thought. Thought is a gravity-like force. According to the General theory of Relativity, gravity is the deformation of space-time. With this definition, however, we can only partially account for the peculiarities of the force of thought. For a complete understanding, we must redefine the concept of gravity; and for this, we must broaden our concept of the "space-time" conceptual system. This broader version can be described as "space-matter" model. Gravity can be regarded as changes in the frequencies of space waves. Thought manifests itself as a gravity-like force, as a new fundamental force. This new force can be given as the changes in the frequencies of space waves, too. Using thought force is possible in our daily practice, too. We can build devices and create methods that are run by thought force.